Serebral palsi tanılı çocuklarda görsel geri bildirim kullanımı ile üst ekstremite eğitimi - KURU ÇOLAK, TUĞBA (My University, 2022)
Purpose: This study aimed to investigate that if upper limb visual feedback training added to the usual therapy was effective on upper limb functions in children with cerebral palsy. Methods: Thirty-eight children with cerebral palsy (4-18 years) participated in the study. The participants were randomly assigned into two groups. Study group (n=19, mean age 8.50±3.40, 53% female) received visual feedback training plus usual therapy twice a week for 8 weeks, 16 sessions in total, while control group (n=19, mean age 10.60±3.80, 42% female) received only usual therapy. The participants’ Gross Motor Function Classification System levels were between I-III and spasticity levels were between ‘0’ to ‘1+’ according to Modified Ashworth Scale. Upper limb range of motion (ROM), grip and pinch strength, hand skills (Minnesota Manual Dexterity Test (MMDT)), and functional abilities (Childhood Health Assessment Questionnaire (CHAQ)) were assessed before and after treatment. Results: The change amount in shoulder flexion (p=0.004) and abduction (p=0.01), supination (p=0.019) and wrist flexion (p=0.004) and extension (p=0.00) ROM values; bilateral MMDT scores (p=0.003) were statistically significantly improved in study group compared to control group. Conclusion: Adding visual feedback training to the usual therapy program of children with cerebral palsy was found to be effective in some outcome measurements such as upper limb ROM and hand skills. In the long-term rehabilitation process, this new training method may be an alternative additive option for children, families, and physiotherapists.

Amaç: Bu çalışmanın amacı, serebral palsi tanısı olan çocuklarda rutin tedaviye eklenen üst ekstremite görsel geribildirim eğitiminin üst ekstremite fonksiyonları üzerine etkisini araştırmaktı. Yöntem: Çalışmaya serebral palsi tanılı (4-18 yaş) 38 çocuk katıldı. Katılımcılar randomize olarak iki gruba ayrıldı. Çalışma grubu (n=19, ortalama yaş 8,50±3,40, %53 kadın) 8 hafta boyunca haftada 2 kez görsel geribildirim eğitimi ve rutin tedavi alırken, kontrol grubu (n=19, ortalama yaş 10,60±3,80, %42 kadın) sadece rutin tedavi aldı. Kaba Motor Fonksiyonel Sınıflandırma Sistemi seviyeleri I-III arasında ve spastisite seviyeleri Modifiye Ashworth Ölçeği’ne göre "0" ile "1+" arasında olan çocuklar çalışmaya dahil edildi. Üst ekstremite hareket açıklığı (EHA), kavrama ve çimdik gücü, el becerileri (Minnesota Manual Dexterity Test (MMDT)) ve fonksiyonel yetenekler (Childhood Health Assessment Questionnaire (CHAQ)) tedavi öncesi ve sonrasında değerlendirildi. Bulgular: Çalışma grubunda omuz fleksiyonu (p=0,004) ve abdüksiyon (p=0,01), supinasyon (p=0,019) ve bilek fleksiyonu (p=0,004) ve ekstansiyon (p=0,00) EHA değerleri; bilateral MMDT puanları (p=0,003) kontrol grubuna göre istatistiksel olarak anlamlı şekilde gelişti. Sonuç: Görsel geribildirim eğitimini serebral palsi tanısı ile rehabilitasyon uygulanan çocukların tedavi programına eklemenin üst ekstremite EHA ve el becerileri gibi bazı sonuç ölçümlerinde etkili olduğu bulundu. Uzun süreli rehabilitasyon sürecinde bu yeni yöntem çocuklar, aileler ve fizyoterapistler için tedaviye eklenebilecek alternatif bir seçenek olabilir.
Keywords: Cerebral palsy; Upper limb; Rehabilitation; Feedback